Concrete curing monitoring using polymer optical fibre Bragg grating sensors - Posporis, Andreas; Ioannou, Andreas; Melo, José Miranda; Antunes, Paulo F.C.; Varum, H.; Marques, Carlos Alberto F.; Kalli, Kyriacos (My University, 2023)
A novel prototype sensing device based on polymer (CYTOP-XYLEX) optical fibre Bragg grating sensors was developed to monitor temperature and relative humidity levels of reinforced concrete from its initial curing phase to a prolonged period. The prototype can be used for concrete quality control offering numerous advantages, such as small size, robustness, high sensitivity, and low-cost continuous in-situ measurements.
Keywords: concrete curing; fibre Bragg grating sensors; Polymer optical fibre; relative humidity; temperature